Automation of Singapore general election polling process by ethereum smart contract - Dong, Aiqing (2019)
Blockchain, as an emerging technology, has become one of the hottest issues of discussion among researchers and businessmen. Different from traditional centralized database architecture where applications use central servers and databases under the authority’s control for information processing, blockchain proposes distributed digital ledgers to store data. This project explores the possibility of using blockchain technology to automate the Singapore general election polling process. Ethereum is chosen to be the blockchain protocol in this case due to its capability in executing smart contracts. For this approach, a smart contract defining general election process will be deployed to a Ethereum blockchain. Users will then connect to the network to monitor the contract. The main advantage of blockchain over the traditional client-server model in this context is system transparency and integrity which enhances the trust level citizens can place on the polling process. However, the fully distributed blockchain approach requires a huge amount of citizen data to be transferred to the distributed ledger for identity verification, which is practically infeasible in a short run due to the amount of work involved as well as citizens’ concern over privacy. In the eyes of this consideration, this project proposes a hybrid model combining the traditional centralized approach for identity verification and access control and the distributed approach for voting.